REPRESENTASI NILAI PENDIDIKAN ISLAM DALAM CERAMAH DIGITAL USTADZ KHALID BASALAMAH: PENDEKATAN ANALISIS WACANA KRITIS FAIRCLOUGH - Malikha, Usrin (LPPI Universitas Al-Qolam Malang, 2025)
Abstract This study analyzes the representation of Islamic educational values in Ustadz Khalid Zeed Abdullah Basalamah’s digital sermons using Fairclough’s Critical Discourse Analysis. Employing a qualitative download–note method, the research examines sermon data from 2022–2024. The findings reveal that Basalamah’s sermons represent values of monotheism, ethics, knowledge, and social responsibility through assertive and educative religious language. His discourse fosters moral and spiritual awareness among digital audiences and integrates textual, discursive, and social dimensions of Islamic preaching. These results support Nurdin and Fauzan’s (2025) view that digital da’wah functions as moral education for contemporary Muslim society. Keywords: Islamic education, digital sermons, Khalid Basalamah, critical discourse analysis